Green Branding Research Through a Bibliometric Lens - Loso Judijanto (Westscience Press, 2026)
This bibliometric study systematically analyzes the evolving landscape of green branding research, focusing on the intersection of sustainability and branding strategies. Using data from Scopus and Web of Science, the study employs bibliometric techniques such as co-citation analysis, keyword co-occurrence, and network visualization to map trends, key concepts, and intellectual structures in the field. The findings highlight the increasing importance of sustainability, green branding, and consumer behavior as core themes driving the development of green branding strategies. The study also underscores the challenges of greenwashing and the growing need for authenticity in green marketing to foster consumer trust. Furthermore, the analysis reveals a global collaboration pattern, indicating the widespread recognition of the need for sustainable practices across industries and regions. However, the study suggests that peripheral areas like place branding and ecotourism offer opportunities for further exploration in future research.⁠